2015
DOI: 10.4103/0257-7941.171677
|View full text |Cite
|
Sign up to set email alerts
|

Thai traditional massage: Issues causing possible adverse effects

Abstract: Thai traditional massage is a widely used massage technique in Thailand and is presently accepted by local Thai Ministry of Public Health. The technique is promoted but not well accepted internationally. There is a concern about the effectiveness as well as safety of this local wisdom. After a recent episode of concurrent acute heart attack and Thai traditional massage in a patient, the issue of possible adverse effects of Thai traditional massage is being widely discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Thai massage shops are widely used techniques and are currently accepted by the local Thai Ministry of Public Health. This local healthcare service is promoted but is not internationally accepted as a healthcare service 15 ) . The effectiveness of Thai massages has been examined in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thai massage shops are widely used techniques and are currently accepted by the local Thai Ministry of Public Health. This local healthcare service is promoted but is not internationally accepted as a healthcare service 15 ) . The effectiveness of Thai massages has been examined in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Most published research has used CSTM protocols, which have been reported to reduce pain intensity, increase the pain pressure threshold (PPT), increase range of motion and body flexibility, and improve quality of life [ 10 , 13 , 25 ]. However, there are also published studies in which TTM has been reported to have no beneficial effects in the treatment of OS [ 26 ]. The disparity in results is potentially because of different criteria having been used to define OS, use of different TTM protocols, and variations in the skill and experience of the TTM therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Burynski (2010) wrote a thorough article on the history and techniques of Thai massage, and how it can be a lucrative addition to a Western massage therapy practice (Burynski, 2018). While Wiwanitkit (2015) studied the possible adverse side effects from Thai massage after a person had a heart attack while receiving a Thai massage. Wiwanitkit concluded the issue needs further study, and there needs to be standardization in the practice of Thai massage (Wiwanitkit, 2015).…”
Section: Aspects Of Thai Culture In the Academic Literaturementioning
confidence: 99%
“…While Wiwanitkit (2015) studied the possible adverse side effects from Thai massage after a person had a heart attack while receiving a Thai massage. Wiwanitkit concluded the issue needs further study, and there needs to be standardization in the practice of Thai massage (Wiwanitkit, 2015).…”
Section: Aspects Of Thai Culture In the Academic Literaturementioning
confidence: 99%